2018
DOI: 10.1186/s13005-018-0180-6
|View full text |Cite
|
Sign up to set email alerts
|

Myositis ossificans traumatica of the masticatory muscles: etiology, diagnosis and treatment

Abstract: BackgroundMyositis ossificans describes a heterotopic bone formation within a muscle. Thereby myositis ossificans is classified in two different groups: myositis ossificans progressiva (MOP) which describes a genetic autosomal dominant rare disease and myositis ossificans traumatica (MOT). The exact pathogenesis of MOT is unclear. The aim of this article was to analyse and interpret the existing literature reporting MOT of masticatory muscles and compare the results with our own clinical experience with MOT. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 53 publications
0
23
0
2
Order By: Relevance
“…The patient of the present case report underwent two surgeries as follows: Coronoidectomy on the left side in 2011 and excision of calcified lesion and buccal fat pad reconstruction in 2013. Complete excision of the ossified mass appears to be a generally accepted treatment for this disease (12). Following removal of the ossified mass, inter-positional fat graft is used as a means of reconstruction by a limited number of surgeons (13).…”
Section: Discussionmentioning
confidence: 99%
“…The patient of the present case report underwent two surgeries as follows: Coronoidectomy on the left side in 2011 and excision of calcified lesion and buccal fat pad reconstruction in 2013. Complete excision of the ossified mass appears to be a generally accepted treatment for this disease (12). Following removal of the ossified mass, inter-positional fat graft is used as a means of reconstruction by a limited number of surgeons (13).…”
Section: Discussionmentioning
confidence: 99%
“…Los reportes de involucro de la región maxilofacial son escasos, siendo el masetero el músculo más comúnmente afectado seguido del temporal y en raras ocasiones el pterigoideo medial o lateral. Hanisch et al 22 , publicó una revisión sistemática y reporte de 21 casos de compromiso del músculo pterigoideo medial a nivel mundial, siendo esta la mayor serie informada, sin embargo, no incluye ningún paciente de la región Latinoamérica.…”
Section: Discussionunclassified
“…La realización de estudios complejos tales como tomografía axial computariza y resonancia magnética ayudan a delimitar la localización extraesquelética, extensión de la lesión, y son utilizadas para hacer una adecuada planeación quirúrgica, dado que ayudan a delimitar la zona y el patrón de mineralización con mayor precisión 20,21 . Debe realizarse después de la tercera semana y suele identificarse un área hiperdensa producida por las calcificaciones que rodea a una lesión central de densidad variable 22 . Dado estos hallazgos no es necesaria la confirmación histopatológica previa a la resección quirúrgica, la cual es el tratamiento de elección.…”
Section: Introductionunclassified
“…The onset of MOT in the medial pterygoid muscle is said to be rare [12]. Previous studies report have suggested that the cause of the MOT was profound trauma [13] [14] [15] [16]. There are no descriptions of trauma caused solely by mastication of hard food.…”
Section: Discussionmentioning
confidence: 99%